2002
DOI: 10.1295/polymj.34.209
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thermally Cross-Linkable Fluorine-containing Poly(aryl ether ketone)s I. Phenylethynyl Terminated Poly(aryl ether ketone)s

Abstract: ABSTRACT:Fluorine-containing poly(aryl ether ketone)s (PEKs) derived from 2,3,4,5,6-pentafluorobenzoic acid (PFBA) exhibit outstanding solubility, thermal stability, low dielectric constant, low moisture absorption and high transparency. Hence, they are expected to be available for optical and electric materials. In such applications, excellent solubility is of great advantage for making thin film and coating. Contrary to this advantage, this is of disadvantage from a point of solvent resistance. Thermally cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…However, the rate of increase of T g decreased as the time was extended when the polymer was cured at any of the above curing temperatures, which was reflected through the respective comparison of tan 1 θ (tan 1 θ ′ = tan 1 θ ′′ > tan 1 θ ′′′), of tan 2 θ (tan 2 θ ′ > tan 2 θ ′′ > tan 2 θ ′′′) and of tan 3 θ (tan 3 θ ′ > tan 3 θ ′′ > tan 3 θ ′′′). This result agreed with the report by Yamashita and colleagues, where it was concluded that the mobility of molecular chains decreases upon increasing the conversion of the crosslinking reaction and therefore it results in a decrease in the reaction rate …”
Section: Resultssupporting
confidence: 93%
“…However, the rate of increase of T g decreased as the time was extended when the polymer was cured at any of the above curing temperatures, which was reflected through the respective comparison of tan 1 θ (tan 1 θ ′ = tan 1 θ ′′ > tan 1 θ ′′′), of tan 2 θ (tan 2 θ ′ > tan 2 θ ′′ > tan 2 θ ′′′) and of tan 3 θ (tan 3 θ ′ > tan 3 θ ′′ > tan 3 θ ′′′). This result agreed with the report by Yamashita and colleagues, where it was concluded that the mobility of molecular chains decreases upon increasing the conversion of the crosslinking reaction and therefore it results in a decrease in the reaction rate …”
Section: Resultssupporting
confidence: 93%